Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 47476 by hassentimol last updated on 10/Nov/18

How may I prove the following theorem ?       ((a + b)/2)   ≥  (√( ab  ))    Thank you

HowmayIprovethefollowingtheorem?a+b2abThankyou

Commented by prakash jain last updated on 11/Nov/18

This is true only for a,b≥0

Thisistrueonlyfora,b0

Answered by Joel578 last updated on 11/Nov/18

Assume a, b ∈ R, then (√a) , (√b) ∈ R  Observe that for all (√a) , (√b) ∈ R  ((√a) − (√b))^2  ≥ 0  ⇔ a − 2(√(ab)) + b ≥ 0  ⇔ a + b ≥ 2(√(ab))  ⇔ ((a + b)/2) ≥ (√(ab))  Hence, proved

Assumea,bR,thena,bRObservethatforalla,bR(ab)20a2ab+b0a+b2aba+b2abHence,proved

Commented by hassentimol last updated on 11/Nov/18

  Thank you sir !  It is also very helpful !

Thankyousir!Itisalsoveryhelpful!

Answered by .... last updated on 10/Nov/18

since (a−b)^2 ≥0  ⇒a^2 +b^2 −2ab≥0  ⇒a^2 +b^2 −2ab+4ab≥0+4ab  ⇒a^2 +b^2 +2ab≥4ab  ⇒(a+b)^2 ≥4ab  ⇒(a+b)≥2(√(ab))  ⇒((a+b)/2) ≥(√(ab))      ((/)/)

since(ab)20a2+b22ab0a2+b22ab+4ab0+4aba2+b2+2ab4ab(a+b)24ab(a+b)2aba+b2ab

Commented by hassentimol last updated on 11/Nov/18

  Thank you sir.  It is very helpful !

Thankyousir.Itisveryhelpful!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com